A collaboration of school administrators and a university faculty to advance school administrator practices using appreciative inquiry. Issue 2 (9th March 2015) - Calabrese, Raymond
Abstract : Purpose: – An appreciative inquiry (AI) collaborative study with 11 school administrators in a highly diverse suburban school district sought to understand if observing and sharing successful school practices/events in a whole group setting led to change in their perceptions, attitudes, and administrative practice. The paper aims to discuss these issues. Design/methodology/approach: – The study took place over a ten-week period with a group of self-selected (voluntary participation) school administrative participants. Findings: – There were two findings: the AI focus of inquiry on successful practices/events shapes school administrator perceptions, attitudes, and application of craft knowledge to practice; and the school administrators' sharing of successful practices/events in a whole group setting generated new forms of practice during the ten-week study. Originality/value: – The findings suggest that reflection and integration of successful practices/events are a source of craft knowledge advancing changes in school administrative practice.